Sickle Cell Trait Protects Against Plasmodium falciparum Infection - Billo, Mounkaila A. (Oxford University Press, 2012)
Although sickle cell trait protects against severe disease due to Plasmodium falciparum, it has not been clear whether sickle trait also protects against asymptomatic infection (parasitemia). To address this question, the authors identified 171 persistently smear-negative children and 450 asymptomatic persistently smear-positive children in Bancoumana, Mali (June 1996 to June 1998). They then followed both groups for 2 years using a cohort-based strategy. Among the 171 children with persistently negative smears, the median time for conversion to smear-positive was longer for children with sickle trait than for children without (274 vs. 108 days, P < 0.001; Cox hazard ratio = 0.56, 95% confidence interval: 0.33, 0.96; P = 0.036). Similar differences were found in the median times to reinfection after spontaneous clearance without treatment (365 days vs. 184 days; P = 0.01). Alternatively, among the 450 asymptomatic children with persistently positive smears, the median time for conversion to smear-negative (spontaneous clearance) was shorter for children with sickle trait than for children without (190 vs. 365 days; P = 0.02). These protective effects of sickle trait against asymptomatic P. falciparum infection under conditions of natural transmission were demonstrable using a cohort-based approach but not when the same data were examined using a cross-sectional approach.